Implementasi Manajemen Pembaharuan Sistem Pendidikan Islam di MTs Negeri 1 Pringsewu; Studi Kasus - Dini Pepilina (Departement of Mathematics Education, 2022)
This case study aims to analyze and evaluate the implementation of the Islamic education renewal management system at MTs Negeri 1 Pringsewu. This study uses a qualitative approach with a case study method and data from observation, interviews, and documentation. The results showed that MTs Negeri 1 Pringsewu had made various efforts to reform the Islamic education system, including curriculum development, improving the quality of human resources, and utilizing information technology. In curriculum development, schools have adopted the 2013 curriculum and developed extracurricular programs to optimize students' potential. Improving the quality of human resources is done through training and competency development for teachers and education staff, implementing a performance appraisal system and providing incentives for teachers who succeed in achieving targets. Utilization of information technology is also one of the efforts made by providing internet facilities and computer laboratories to support the learning process and curriculum development. However, there are still several obstacles in implementing Islamic education system reform management, such as limited resources and challenges in using information technology. With systematic and integrated management efforts, MTs Negeri 1 Pringsewu improved the quality of Islamic education held at the school.